ECOLOGICAL INTELLIGENCE OF COASTAL COMMUNITY ON BIODIVERSITY CONSERVATION (Case Study of Bajau Coastal Communities, Gorontalo) - Ramli Utina (Prodi Magister Ilmu Biologi, Fakultas MIPA, Universitas Udayana, 2017)
Human behavior is a part of the ecological system, therefore overcoming the ecological crisis and living resources need to explore human traditions, way of life and human behavior toward natural resources. Understanding and translation of human harmonious relationship with all elements along with other living beings is a form of human ecological intelligence. The objective of this study was to describe the traditions and coastal communities behavior that contains the value of ecological intelligence in coastal biodiversity conservation. The study was based on observation, focus group discussion and identification of Bajau coastal community tradition in their lives and livelihoods on fishing, as well as the behavior toward biological resources. Bajau coastal communities settled in three villages in Pohuwato regency, Gorontalo. There are two themes that contains the value of ecological intelligence of Bajau communities in the conservation of biodiversity, namely; mamia kadialo in tradition of fishing, and fishing behavior. The prohibition in the tradition of mamia kadialo contains the value of conservation of biodiversity. Usage of simple equipment on fishing activities provide a positive ecological consequences for the conservation of coastal biodiversity.